2014
DOI: 10.4103/2230-8210.137512
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D levels and microvascular complications in type 2 diabetes

Abstract: Background:Vitamin D has important actions on glucose metabolism. These include improved insulin exocytosis, direct stimulation of insulin receptor, improved uptake of glucose by peripheral tissues, improving insulin resistance. It has got various pleiotropic effects like suppression of cell mediated immunity, regulation of cell proliferation, stimulation of neurotropic factors such as nerve growth factor, Glial cell line-derived neurotrophic factor, neurotropin, suppression of RAAS, reduction of albuminuria, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
64
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(76 citation statements)
references
References 28 publications
10
64
0
2
Order By: Relevance
“…Our results regarding 25-(OH)D was significantly correlated with albuminuria in Chinese type 2 diabetic patients are consistent with several clinical studies that have reported that low 25-(OH)D levels were associated with an increased risk of albuminuria in diabetic and non-diabetic patients [18][19][20]. Direct cellular effects of vitamin D deficiency, including podocyte loss and increasing glomerulosclerosis, may be contributing to the increasing risk of albuminuria [10].…”
Section: Discussionsupporting
confidence: 93%
“…Our results regarding 25-(OH)D was significantly correlated with albuminuria in Chinese type 2 diabetic patients are consistent with several clinical studies that have reported that low 25-(OH)D levels were associated with an increased risk of albuminuria in diabetic and non-diabetic patients [18][19][20]. Direct cellular effects of vitamin D deficiency, including podocyte loss and increasing glomerulosclerosis, may be contributing to the increasing risk of albuminuria [10].…”
Section: Discussionsupporting
confidence: 93%
“…Vitamin D has been shown to have a neuroprotective effect (15) and to be implicated in the pathogenesis of diabetes mellitus (13,16) and a low level of vitamin D in patients with DN may simply indicate its insufficiency in patients with diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have compared 25(OH)D concentrations between groups of individuals with and without diabetic retinopathy in case–control designs [3, 11, 13, 17, 22] with a protective association of 25(OH)D on prevalent retinopathy found in three studies [3, 11, 13]. The majority of other studies consist of cross-sectional designs recruiting participants from clinical settings [5, 6, 9, 10, 12, 14, 15, 19, 21, 23] with half of these studies supporting a protective association of vitamin D with retinopathy [5, 6, 9, 10, 12].…”
Section: Discussionmentioning
confidence: 99%